Short-term outcome after simultaneous pancreas-kidney transplantation with alemtuzumab vs. basiliximab induction: a single-center retrospective study - Tim D. A. Swaab; Robert A. Pol; Meindert J. Crop; Jan-Stephan F. Sanders; Stefan P. Berger; Hendrik S. Hofker; Stephan J. L. Bakker; Charlotte A. te Velde-Keyzer (Scientific Reports)
Abstract During the COVID-19 pandemic our center adjusted the standard induction therapy for normal immunological risk simultaneous pancreas-kidney (SPK) transplantations from T-cell depletion by alemtuzumab (ALEM) to IL-2 receptor blocking by basiliximab (IL2R). Here, we analyze the impact of this change on 1 year post-transplantation outcomes. Thirty-six adult patients who underwent SPK transplantation between June 2015 and June 2023 were included, of whom 21 before February 2020 (ALEM) and 15 after February 2020 (IL2R). Patients were stratified into two groups based on the induction therapy received. One death occurred during the follow up period. A total of three pancreas and two kidney grafts were lost. No differences between kidney and pancreas graft function or rejection rates were observed. Patients receiving IL2R induction had significantly lower 30 day postoperative complication rates (34 vs. 46%, p = 0.03) and experienced fewer bacterial infections (< 6 months: 47 vs. 81%, p = 0.03). Additionally, lower rates of viral (including CMV) and fungal infections were observed. IL2R patients also had a significantly shorter hospital admission durations (14 vs. 30 days, p < 0.001). In conclusion, IL2R induction in SPK recipients was associated with similar short-term graft function and potentially improved outcomes compared to ALEM, warranting cautious interpretation due to sample size.